2016
DOI: 10.1371/journal.pone.0161597
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Blast Exposure Conditions in the Shock Tube for Generating Pure, Primary Shock Waves: The End Plate Facilitates Elimination of Secondary Loading of the Specimen

Abstract: The end plate mounted at the mouth of the shock tube is a versatile and effective implement to control and mitigate the end effects. We have performed a series of measurements of incident shock wave velocities and overpressures followed by quantification of impulse values (integral of pressure in time domain) for four different end plate configurations (0.625, 2, 4 inches, and an open end). Shock wave characteristics were monitored by high response rate pressure sensors allocated in six positions along the len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Chandra et al studied the shock evolution within and outside shock tubes, concluding that the placement of a test article outside of the open end of a shock tube exposed the test article to complex flow phenomena that were not representative of blast waves in the field (3). Kuriakose et al, Yu et al, and Needham et al, also studied the effects of the test article's placement and whether end-jet testing provided representative results (8)(9)(10). Kuriakose et al (8) and Needham et al (10) agreed with Chandra's conclusions, while Yu et al (9) concluded that end-jet testing was acceptable under specific constraints.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Chandra et al studied the shock evolution within and outside shock tubes, concluding that the placement of a test article outside of the open end of a shock tube exposed the test article to complex flow phenomena that were not representative of blast waves in the field (3). Kuriakose et al, Yu et al, and Needham et al, also studied the effects of the test article's placement and whether end-jet testing provided representative results (8)(9)(10). Kuriakose et al (8) and Needham et al (10) agreed with Chandra's conclusions, while Yu et al (9) concluded that end-jet testing was acceptable under specific constraints.…”
Section: Introductionmentioning
confidence: 87%
“…Kuriakose et al (8) and Needham et al (10) agreed with Chandra's conclusions, while Yu et al (9) concluded that end-jet testing was acceptable under specific constraints. Specifically, Yu et al concluded that testing inside is acceptable as long as the test article is placed at least 8-10 shock tube diameters down the driven section, measured from the diaphragm, and testing outside is acceptable as long as the test article is placed within ½ a tube diameter from the exit of the shock tube (3,8,9). When testing inside, another important consideration is the blockage, "the ratio of the total 'presented area' of the obstruction relative to the crosssection of the tube, " and Needham et al found that the blockage should not exceed 10-25% depending on the exact nature of the experiment (10).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid expansion of the shock front at the shock tube exit causes a density gradient to form, which initiates the rarefaction wave. Previously, we have shown that a reflection generated from a reflector plate at an appropriate offset can largely nullify the impact of the rarefaction wave on the incident waveform within the shock tube [29]. A normal reflection of the shock on a perpendicular endplate causes a reflected compressive wave that greatly reduces the effect of the tensile rarefaction wave.…”
Section: Rarefaction Wavementioning
confidence: 99%
“…The shock tube used in this work has been validated to reproduce free-field explosions within the test section accurately at sensor location I3 in Fig 2 (230 x 230 mm 2 square cross-section, 6 m in length) [29,30]. Briefly, compressed helium within a 55 cm length, 10 cm diameter chamber is separated from atmospheric-pressure air by Mylar membranes.…”
Section: Validation Datasetmentioning
confidence: 99%
See 1 more Smart Citation